Jane Austen and Modernization - Thompson, J. author. aut Link
X, 211 p.
Keywords: Jane Austen wrote when sociology was being established as the new discipline to understand social issues such as urbanization and industrialization. Drawing on landmark sociologists such as Durkheim and Bourdieu, this study argues that the novels of Austen were heavily influenced by these early developments in sociology.